2021
DOI: 10.1371/journal.pone.0254223
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characters and influence factors of hand, foot and mouth epidemic in Xinjiang, China

Abstract: Hand, foot and mouth (HFM) disease is a common childhood illness. The paper aims to capture the spatiotemporal characters, and investigate the influence factors of the HFM epidemic in 15 regions of Xinjiang province from 2008 to 2017, China. Descriptive statistical analysis shows that the children aged 0-5 years have a higher HFM incidence, mostly boys. The male-female ratio is 1.5:1. Through the scanning method, we obtain the first cluster high-risk areas. The cluster time is usually from May to August every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The onset season seen in 2020-2021 was different from that of previous years, consistent with the Japanese experience of HFMD [26]. HFMD incidence was concentrated in autumn and winter, perhaps due to COVID-19, and was related to population mobility, social economy and policy factors [27]. Therefore, limiting assembly of susceptible populations and implementing prevention and control policy measures may regulate the seasonal distribution of HFMD and reduce morbidity.…”
Section: Discussionsupporting
confidence: 53%
“…The onset season seen in 2020-2021 was different from that of previous years, consistent with the Japanese experience of HFMD [26]. HFMD incidence was concentrated in autumn and winter, perhaps due to COVID-19, and was related to population mobility, social economy and policy factors [27]. Therefore, limiting assembly of susceptible populations and implementing prevention and control policy measures may regulate the seasonal distribution of HFMD and reduce morbidity.…”
Section: Discussionsupporting
confidence: 53%
“…• Based on the AIC and BIC criteria, we conduct multiple order combinations to determine the optimal parameters. To capture the nonlinear characteristics embedded in the residuals of the SARIMA(p, d, q) × (P, D, Q) s model in Table 3, the meteorological variables corresponding to each region are used as input variables for the XGBoost algorithm ( 8)- (10). In the training of the XGBoost algorithm, the parameters have a significant impact on the effectiveness of the training.…”
Section: Analysis Of Sarima-xgboost Modelmentioning
confidence: 99%
“…According to the transmission mechanism of infectious diseases, meteorological conditions may influence the incidence, the transmission range, and the susceptibility of the population to diseases [5][6][7] . Various studies have shown that meteorological factors such as temperature, rainfall, humidity, air pressure, light, and wind speed are tightly associated with HFMD [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous prior studies on the spatiotemporal pattern of HFMD (6)(7)(8)(9)(10)(11). Nevertheless, the majority of the related researches have been carried out in just one province or local region with a small spatial size, such as Shaanxi Province (12), Xinjian (6), Henan Province (13), or the Ili River Valley Region (14).…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous prior studies on the spatiotemporal pattern of HFMD (6)(7)(8)(9)(10)(11). Nevertheless, the majority of the related researches have been carried out in just one province or local region with a small spatial size, such as Shaanxi Province (12), Xinjian (6), Henan Province (13), or the Ili River Valley Region (14). Analysis of the spatial distribution and temporal trend of HFMD incidence nationwide helps to determine high-risk provinces and periods, thus identifying provinces where prevention and control efforts are most needed and maximizing and rationalizing the utilization of limited public health resources.…”
Section: Introductionmentioning
confidence: 99%